Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Cách 1: y' = (9 -2x)'(2x3- 9x2 +1) +(9 -2x)(2x3- 9x2 +1)' = -2(2x3- 9x2 +1) +(9 -2x)(6x2 -18x) = -16x3 +108x2 -162x -2.
Cách 2: y = -4x4 +36x3 -81x2 -2x +9, do đó
y' = -16x3 +108x2 -162x -2.
b) y' = .(7x -3) +
(7x -3)'=
(7x -3) +7
.
c) y' = (x -2)'√(x2 +1) + (x -2)(√x2 +1)' = √(x2 +1) + (x -2) = √(x2 +1) + (x -2)
= √(x2 +1) +
=
.
d) y' = 2tanx.(tanx)' - (x2)' =
.
e) y' = sin
=
sin
.
![](https://rs.olm.vn/images/avt/0.png?1311)
16.
\(y'=\frac{\left(cos2x\right)'}{2\sqrt{cos2x}}=\frac{-2sin2x}{2\sqrt{cos2x}}=-\frac{sin2x}{\sqrt{cos2x}}\)
17.
\(y'=4x^3-\frac{1}{x^2}-\frac{1}{2\sqrt{x}}\)
18.
\(y'=3x^2-2x\)
\(y'\left(-2\right)=16;y\left(-2\right)=-12\)
Pttt: \(y=16\left(x+2\right)-12\Leftrightarrow y=16x+20\)
19.
\(y'=-\frac{1}{x^2}=-x^{-2}\)
\(y''=2x^{-3}=\frac{2}{x^3}\)
20.
\(\left(cotx\right)'=-\frac{1}{sin^2x}\)
21.
\(y'=1+\frac{4}{x^2}=\frac{x^2+4}{x^2}\)
22.
\(lim\left(3^n\right)=+\infty\)
11.
\(\lim\limits_{x\rightarrow1^+}\frac{-2x+1}{x-1}=\frac{-1}{0}=-\infty\)
12.
\(y=cotx\Rightarrow y'=-\frac{1}{sin^2x}\)
13.
\(y'=2020\left(x^3-2x^2\right)^{2019}.\left(x^3-2x^2\right)'=2020\left(x^3-2x^2\right)^{2019}\left(3x^2-4x\right)\)
14.
\(y'=\frac{\left(4x^2+3x+1\right)'}{2\sqrt{4x^2+3x+1}}=\frac{8x+3}{2\sqrt{4x^2+3x+1}}\)
15.
\(y'=4\left(x-5\right)^3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(y'=42\left(2x+3\right)^{20}\left(x-4\right)^{23}+23\left(x-4\right)^{22}\left(2x+3\right)^{21}\)
b/ \(y=\frac{1}{x\sqrt{x}}=\frac{1}{\sqrt{x^3}}=x^{-\frac{3}{2}}\Rightarrow y'=-\frac{3}{2}x^{-\frac{5}{2}}=-\frac{3}{2x^2\sqrt{x}}\)
c/ \(y'=\frac{\left(x+\frac{1}{x}\right)'}{2\sqrt{\frac{x^2+1}{x}}}=\frac{1-\frac{1}{x^2}}{2\sqrt{\frac{x^2+1}{x}}}=\frac{\left(x^2-1\right)\sqrt{x}}{2x^2\sqrt{x^2+1}}\)
d/ \(y=x^2+x^{\frac{3}{2}}+1\Rightarrow y'=2x+\frac{3}{2}x^{\frac{1}{2}}=2x+\frac{3}{2}\sqrt{x}\)
e/ \(y'=\frac{\sqrt{1-x}+\frac{1+x}{2\sqrt{1-x}}}{1-x}=\frac{3-x}{2\left(1-x\right)\sqrt{1-x}}\)
f/ \(y'=\frac{\sqrt{a^2-x^2}+\frac{x^2}{\sqrt{a^2-x^2}}}{a^2-x^2}=\frac{a^2}{a^2-x^2}\)
a/ \(y'=8x-6\)
b/ \(y'=\left(2x-1\right)cosx-sinx\left(x^2-x+2\right)\)
c/ \(y'=\frac{x+2-\left(x-1\right)}{\left(x+2\right)^2}=\frac{3}{\left(x+2\right)^2}\)
d/ \(y'=-\frac{\left(\sqrt{x^2-x-1}\right)'}{x^2-x-1}=-\frac{2x-1}{2\left(x^2-x-1\right)\sqrt{x^2-x-1}}\)
e/ \(y'=\frac{\left[\left(4-3x^2\right)^5\right]'}{2\sqrt{\left(4-3x^2\right)^5}}=\frac{-15x\left(4-3x^2\right)^4}{\sqrt{\left(4-3x^2\right)^5}}=-15x\sqrt{\left(4-3x^2\right)^3}\)